Evaluación del funcionamiento de la protección diferencial 87 en transformadores monofásicos ante presencia de fallas, mediante un prototipo didáctico - Barahona Vaca, Edgar Geovanny (2022)
In this paper, the construction process of the didactic prototype that allows to evaluate the operation of the differential protection 87 was performed, by means of the parameterization of variables, is compiled. The module uses different components, among which the single-phase transformer stands out as the protected element. In this way, by means of the different elements that integrate the didactic prototype, it is possible to establish the conditions for the performance of the differential protection function 87. For this purpose, several parameters are considered, such as the minimum operating current, the starting current or the operating slope, which, together with the measured data, such as the primary and secondary current, which in turn make it possible to determine the value corresponding to the differential current, have made it possible to emulate the differential protection function 87 and it´s percentage variant. To achieve the above, current sensors of the Arduino brand were used, which together with the Nano microprocessor, of the same brand, will allow data collection, which after processing, will be communicated to LabVIEW where are constant is used, which allows scaling the values obtained in order to develop the programming logic that allows the entry of parameters, selection of CT´s, calculation of the differential and minimum operating current, as well as the identification of the opera9tion zones. Finally, the corresponding documents that allow the interaction with the didactic prototype were elaborated, these are the user´s guide and the practical guide, which allow the user to use the module in an adequate way.